Antibacterial, Antifungal and Anticorrosion Properties of Green Tea Polyphenols Extracted Using Different Solvents - Brindha, ThirumalaiRaj; Rathinam, Ramasamy; Dheenadhayalan, Sivakumar (Asian Journal of Biological and Life Sciences)
The purpose of this study was to examine the antibacterial, antifungal and anticorrosion properties of green tea polyphenols extracted using different solvents like water, 70% ethanol, 70% methanol and dimethyl form amide. The extracted polyphenols were separated using TLC analysis. The antibacterial and antifungal activities were done by well diffusion method and it was found that polyphenols extracted using methanol and ethanol showed increased inhibition activity. Anticorrosion property was investigated using weight loss measurements and showed significant inhibition effect for DMF extract.
Keywords: Anticorrosion property; Antimicrobial activity; Ethanol; Green Tea; Methanol; Polyphenols; TLC analysis